Nursing students’ knowledge and attitudes toward older adults - Castro, Cidália; Antunes, Ricardo; Simoes, Aida; Bernardes, Catarina; Fernandes, Júlio Belo (Frontiers in Public Health, 2023)
Nursing students, as the future healthcare workforce, hold immense potential in providing quality care to older adults and becoming advocates for promoting aging and public health, thus contributing significantly to addressing the multifaceted challenges of our aging society. Nurses’ knowledge and attitudes about aging affect health care quality. Negative and unattractive representations of the social problems associated with aging contaminate nursing students’ attitudes. Nursing schools are challenged to develop new curricula to prepare future nurses for the inherent complexity of an aging society. This study aims to assess the knowledge and attitudes of nursing students toward older adults and identify the variables that can influence these attitudes. Quantitative research was carried out through the application of an online survey using a cross-sectional descriptive research design. A total of 182 nursing students completed the online survey. Progression in the nursing course was statistically significant; the more students advanced, the more positive attitudes and knowledge they revealed about aging; 39% of students have daily contact with their grandparents; however, only 14.8% would like to work with older adults. Multiple linear regression revealed that the most important factor for positive attitudes and knowledge about aging was regular contact with grandparents, followed by progression in the nursing course. The students’ age was not a significant factor in improving attitudes or expanding knowledge regarding older adults. In a multidimensional logic, the deepening of knowledge about aging and the socialization of students with older adults are central factors that should reinforce curricula in nursing education.